Development of E-Learning Module: Historical Culture Society Based on Local Genius - Diky Aprianto; Nurul Umamah; Sumardi Sumardi (History Education, University of Jember, 2017)
A module has the characteristics required by the curriculum of 2013. It is the teaching materials that emphasize student-centered learning paradigm. Curriculum 2013, is a curriculum that aims to build the national character of learners. One of its implementation, which is implementing learning that relates to the needs of the environment around the learner. Thus, they invented the electronic module in the history of Using culture society (local history) as an effort to fulfil the demands of learning in the Curriculum 2013. The purpose of this study was to develop an electronic module validated experts and effectively used as a learning material about the history of Using culture society in tenth-grade high school student in Banyuwangi. This study uses research method of development with Borg & Gall model. Data collection research using techniques of documentation, observation, questionnaires, interviews, and tests. Subjects of this study involving five teachers of historical subjects and 158 tenth grade students from five high school in Banyuwangi. The results of research and development of electronic modules in the history of Using society shows, validation material experts scored 76% were categorized